Introduction to Tourism and Hospitality in BC - Westcott, Morgan; Bird, Geoffrey; Briscoe, Peter (Open textbook library., 2020)
This textbook is an introduction to the tourism and hospitality industry in British Columbia, and is written with a first year college and university audience in mind. It is a collaborative work with input from educators, industry leaders, employers, and past graduates of BC's tourism and hospitality management programs. All chapters have been reviewed by experts in the field. Each chapter is organized thematically moving from a global, then national and finally provincial context. Some chapters are quite global in focus while others concentrate primarily on British Columbia. Chapter content is based on available data and research, and input from collaborators. Each chapter features “Spotlight On” text boxes that highlight an organization, business, or other key component of the chapter's theme. “Take a Closer Look” features encourage students to do further reading on particular subjects. At the end of each chapter, key terms are presented in alphabetical order to help students gain confidence with terminology. These are followed by chapter exercises and a case study for in-depth exploration of the subject matter. Key terms are summarized in a Glossary at the end of the textbook.